Clustering of rare earth in glasses, aluminum effect: experiments and modeling - Monteil, A.; Chaussedent, S.; Alombert-Goget, G.; Gaumer, N.; Obriot, J.; Ribeiro, SJL; Messaddeq, Younes [UNESP]; Chiasera, A.; Ferrari, M. (Elsevier B.V., 2004)
Luminescent spectra of Eu3+-doped sol-gel glasses have been analyzed during the densification process and compared according to the presence or not of aluminum as a codoping ion. A transition temperature from hydrated to dehydroxyled environments has been found different for doped and codoped samples. However, only slight modifications have been displayed from luminescence measurements beyond this transition. To support the experimental analysis, molecular dynamics simulations have been performed to model the doped and codoped glass structures. Despite no evidence of rare earth clustering reduction due to aluminum has been found, the modeled structures have shown that the luminescent ions are mainly located in aluminum-rich domains. The synthesis of both experimental and numerical analyses has lead us to interpret the aluminum effect as responsible for differences in structure of the luminescent sites rather than for an effective dispersion of the rare earth ions. (C) 2004 Elsevier B.V. All rights reserved.